Monetary policy transmission through investment account in Malaysia : pre and post IFSA 2013 - Muhammad Md Husin (Institute of Islamic Banking and Finance (IIiBF), International Islamic University Malaysia, 2020)
This paper sought to identify the monetary policy transmission via the Investment Account (IA) and how it has affected Islamic banks in Malaysia during the pre and post introduction of Islamic Financial Service Act (IFSA) 2013. As the name implies, IA is a type of account meant for investment purpose that bears a unique risk and reward structure compared to interest rate (IR) based deposit account offered by conventional banks. Such differences would eventually lead to a divergence between rate of return (ROR) for IA and IR for conventional deposits. Notwithstanding that, it is interesting to note that under dual banking system practiced in Malaysia, divergence between ROR and IR would create arbitrage opportunity for customers in the banking system and could lead to unintended volatility as the customers could easily switch between IA and IR based deposit. This could also diminish the effectiveness of the monetary policy framework of the central bank. In this regard, this paper seeks to examine how monetary policy stance by Bank Negara Malaysia (BNM) is transmitted through the IA. The study employs the Autoregressive-Distributed Lag (ARDL) techniques to measure the relationships between variables associated with IA, ROR, overnight policy rate (OPR), bond yield, economic output as well as inflation. The period of the study is divided into three different periods which are the full period of study from January 2007 until December 2018, period prior to IFSA introduction from January 2007 to June 2013 and period post IFSA introduction from July 2015 to December 2018. These periods coincide with the evolution of IA which is structured based on Mudharabah contract. The outcome of the ARDL estimates indicate that monetary policy transmission via IA is observed for all three periods, mirroring the scenario seen for similar transmission via interest based conventional deposits. This suggest appropriate response towards monetary policy stance of BNM, exemplified by the long and short-term relationship observed between IA and OPR, which is essential in meeting the objective of the monetary policy implementation. Nevertheless, continued monitoring of the development of Islamic finance, typically on the introduction of unique products and services is required to assess the potential impact on the suitability and the objective of monetary policy implementation.